Faith and Mental Health: Reconstructing the Religious Narrative in Suicide Prevention Efforts in Indonesia (A Narrative Review) - Hafid Algristian; Nur Azizah; Khairunnisa; Zulidiyana Rusnalasari; Damba Bestari (Universitas Muhammadiyah Surabaya, 2026)
Suicide remains a largely hidden public health concern in Indonesia, shaped by pervasive underreporting and religion-based stigma that frequently frames psychological suffering as a manifestation of weak faith. This narrative review critically examines the dual role of religion in suicide prevention, acknowledging its capacity to function both as a protective resource and, under certain interpretive conditions, as a factor that may exacerbate risk through stigma and social exclusion. Rather than aggregating empirical evidence, this review adopts an interpretive and theory-building approach, synthesizing interdisciplinary literature from public health, psychiatry, neurobiology, and Islamic theology to develop a conceptual framework for narrative reconstruction. The analysis highlights that religious teachings can foster hope, meaning, and social belonging, while rigid or judgmental interpretations may intensify shame and hinder help-seeking. Building on this synthesis, the article proposes a normative framework that integrates scientific understandings of psychological pain and neurobiological vulnerability with compassionate theological concepts, such as divine mercy and hope, and with the reinterpretation of ikhtiar and tawakal as supportive of professional mental health care. As a practical illustration, a culturally resonant psychological first aid model—Ask, Listen, Accompany (ALA)—is presented as a community-oriented approach aligned with established global principles, without claiming empirical validation. The framework is intended as a heuristic guide rather than an evidentiary model, and its applicability will vary across Indonesia’s diverse socioreligious contexts. By repositioning religion as complementary to clinical care, this review aims to inform dialogue, guide future empirical research, and support culturally sensitive suicide prevention efforts.